Penerapan Tema Arsitektur Islam pada Rancangan Perpustakaan Umum di Kota Blangpidie, Kab. ABDYA - Muhammad Haikal; Mira Alfitri; T. Eka Panny Hadinata (Bayt ElHikmah: Journal of Islamic Architecture and Locality, 2024)
It is relevant in the world of education, the public library is a place for all activities aimed at increasing learning motivation and interest in reading students and the people of Aceh Barat Daya, Blangpidie and its surroundings support students and the general public with interest in reading. In the application of the building along with the theme raised, it is necessary to collect site analysis so that the transformation of the shape of the building makes the activities of this library building stand out.